FAKTOR-FAKTOR YANG MEMPENGARUHI KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KPP PRATAMA LUBUK PAKAM - Saladin Batubara, Soulthan; Iskandar, Rizal (Universitas Pembangunan Panca Budi, 2025)
The state revenue derived from tax revenue. Tax compliance will have a positive impact to the state revenue. The lack of tax compliance will make it less effective taxation of earned income countries. Tax compliance can be triggered by several factors, namely the taxpayer awareness, knowledge of taxes and tax penalties. This study aims to determine the effect of taxpayer awareness, knowledge of tax and tax penalties against an individual taxpayer compliance in KPP Pratama Surabaya Gubeng. The population of this research is all individual taxpayer on KPP Pratama Surabaya Gubeng and total sample of 100 taxpayers. Methods of data analysis using multiple linear regression analysis. the results showed that awareness is partially taxpayer does not affect taxpayer compliance in implementing tax compliance, while knowledge of tax and tax penalties partially influence on tax compliance in implementing tax compliance. Taken together all of the variables affecting the individual taxpayer compliance in implementing tax compliance.